Interactive Digital Storybooks: A Personalized Approach to English Learning in Indonesian Primary Schools - Himawati, Ulya; Mahendra, Danang; Zulfa , Laila Ngindana; Hamidaturrohmah, Hamidaturrohmah; Herningtyasari, Gadis (Universitas Lancang Kuning, 2025)
In response to the growing emphasis on meaningful and student-centered English instruction in Indonesian primary schools, this study investigates the effectiveness of an Interactive English Story Book in fostering young learners’ engagement, motivation, comprehension, and autonomous learning. This study explores the potential and educational benefits of an Interactive English Story Book aimed at improving engagement, motivation, comprehension, and usability for young learners. A mixed-methods approach was utilized to combine quantitative trends with qualitative insights, facilitating a thorough understanding of learning processes. This design was selected to triangulate perceptual data from students and educators within genuine classroom environments. The investigation included 13 fourth-grade students from a suburban elementary school, serving as a phase to assess feasibility and user feedback. Data collection involved the use of student questionnaires, classroom observations, and interviews. The results indicated a high level of engagement, motivation, and usability, as students reacted favorably to the visual and interactive elements. Some minor comprehension challenges were observed in story contexts that were culturally unfamiliar, and educators reported connectivity issues in rural regions. This study presents a unique approach by integrating digital storytelling, English as a Foreign Language pedagogy, and curriculum reform, validated through mixed-method classroom research. This provides foundational evidence for expanding digital storytelling innovations within Indonesia’s Merdeka Belajar framework and for future longitudinal studies in English as a Foreign Language.